Parametric Study on Spectral Fatigue Analysis of Offshore Jacket Platform with SACS software - Ravichandran, Nalinii (IRC, 2016)
Fatigue analysis is very important in order to obtain the fatigue life of a particular based on fatigue stress cycle. There are two different type of fatigue analysis which are stochastic or finding known as spectral fatigue analysis and deterministic. Spectral fatigue is more reliable as it considers irregular wave condition. Spectral fatigue can be conducted using two different software which are SACS and SESAM.The main objective of this project is to compare the spectral fatigue analysis in SACS and SESAM based on different parameters like wave height, wave period, and diameter of the tubular and others at jacket platform. Besides that, the sensitivity of the parameters between SACS and SESAM for spectral fatigue analysis is also conducted in order to compare and evaluate suitability of these two software based on Malaysia Sea